2021
DOI: 10.1101/2021.09.09.459588
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

B cell-intrinsic requirement for WNK1 kinase in T cell-dependent antibody responses

Abstract: Migration and adhesion play critical roles in B cells, regulating recirculation between lymphoid organs, migration within lymphoid tissue and interaction with CD4+ T cells. However, there is limited knowledge of how B cells integrate chemokine receptor and integrin signaling with B cell activation to generate efficient humoral responses. Here we show that the WNK1 kinase, a regulator of migration and adhesion, is essential in B cells for T-dependent antibody responses. We demonstrate that WNK1 transduces signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…We previously showed that loss of WNK1 slows down the homing of both CD4 + and CD8 + T cells to secondary lymphoid organs, and impairs CXCL12-induced migration of CD4 - CD8 - thymocytes 6, 28 . More recently we found that WNK1 is required for CXCL13-induced migration of B cells and their in vivo migration in lymph nodes 29 . Furthermore, previous studies have shown that inhibition of the sodium-hydrogen exchanger NHE-1 (SLC9A1) or AQP9 decreases fMLP-induced migration of human neutrophils, and SLC12A2 inhibition reduces migration of glioblastoma cells, indicating that ion and water movement may be important for migration in multiple contexts 3032 .…”
Section: Discussionmentioning
confidence: 92%
“…We previously showed that loss of WNK1 slows down the homing of both CD4 + and CD8 + T cells to secondary lymphoid organs, and impairs CXCL12-induced migration of CD4 - CD8 - thymocytes 6, 28 . More recently we found that WNK1 is required for CXCL13-induced migration of B cells and their in vivo migration in lymph nodes 29 . Furthermore, previous studies have shown that inhibition of the sodium-hydrogen exchanger NHE-1 (SLC9A1) or AQP9 decreases fMLP-induced migration of human neutrophils, and SLC12A2 inhibition reduces migration of glioblastoma cells, indicating that ion and water movement may be important for migration in multiple contexts 3032 .…”
Section: Discussionmentioning
confidence: 92%